Hypothyroidism among children and adolescents with nephrotic syndrome in Mulago National Referral Hospital, Kampala, Uganda; a cross-sectional study - Maureen Tumwesige; Joseph Rujumba; Thereza Piloya; Judith Caroline Aujo (BMC, 2024)
Abstract Background Nephrotic syndrome (NS) is the commonest glomerular disease among children. It is characterized by heavy proteinuria and is a risk factor for hypothyroidism in the affected children. Hypothyroidism is of concern because it affects the physical and intellectual development of children and adolescents. This study sought to establish the prevalence and factors associated with hypothyroidism among children and adolescents with NS. Methods A cross-sectional design was used to study 70 children and adolescents aged 1-19 years diagnosed with nephrotic syndrome and being followed up in the kidney clinic in Mulago National Referral Hospital. Questionnaires were used to collect patients' socio-demographics and clinical information. A blood sample was taken for analysis for thyroid stimulating hormone (TSH) and free thyroxine (FT4), renal function tests and serum albumin. Hypothyroidism included both overt and subclinical forms. Overt hypothyroidism was defined as TSH level > 10 mU/L and FT4 < 10pmol/L, or FT4 < 10pmol/l with normal TSH, or TSH < 0.5mU/l. Sub-clinical hypothyroidism was defined as TSH ranging between 5 and10 mU/L with normal age appropriate FT4 levels. Urine samples were collected and taken for a dipstick examination. The data was analyzed using STATA version 14. The Bayesian Logistic regression analysis approach was used to estimate odds ratios (OR) and their associated 95% credible intervals. All predictor variables with p value < 0.05 at frequentist statistical analysis were considered significant. Results The mean age (standard deviation) of participants was 9 years (3.8). There were more males; 36 of 70 (51.4%). The prevalence of hypothyroidism was 23% (16/70 participants). Of the 16 children with hypothyroidism, 3 (18.7%) had overt hypothyroidism while 13 had subclinical hypothyroidism. Only low serum albumin was found to be strongly associated with hypothyroidism; Bayesian OR 132.57 (CI 9.13-567.10) with a frequentist OR of 37 and a p value of 0.001. Conclusion The prevalence of hypothyroidism among children and adolescent with nephrotic syndrome attending Mulago Hospital paediatric kidney clinic was 23%. Hypoalbuminemia was found to be associated with hypothyroidism. Therefore, children and adolescents that have severely low levels of serum albumin should be screened for hypothyroidism and linked to endocrinologists for care.